IMPLEMENTATION OF MODIFIED NETWORK PORT SCANNER FOR WINDOWS BASED OPERATING SYSTEMS: IMPLEMENTATION OF MODIFIED NETWORK PORT SCANNER FOR WINDOWS BASED OPERATING SYSTEMS - Boyanov, Petar (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
In this paper a modified network port scanner for Windows based operating systems implementing a linear algorithm is developed.